The uptake of key elements of sexual and reproductive health services and its predictors among rural adolescents in Southern Ethiopia, 2020: application of a Poisson regression analysis - Aklilu Habte; Samuel Dessu (BMC, 2023)
Plain language summary Progress towards universal health coverage requires keeping adolescents healthy, as adolescence represents a significant opportunity for successful prevention and health promotion with life-course implications. Sexual and reproductive health (SRH) service is well described as the combination of techniques, procedures, and services that prevent and respond to sexual health snags by ensuring sexual health and well-being. While most adolescent health problems are avertible or fixable, adolescents face many hurdles in accessing health care and information, especially those who are in rural corners. Although 25% of the Ethiopian population is young, Sexual and Reproductive Health (SRH) Services have not been adequately researched and intervened, leaving adolescents with many reproductive health challenges. Assessment of the uptake of each element of SRH service and its determinants among those age groups is essential to improving service uptake and reducing the burden of illness and disability in adolescents. Thus, this study aimed at assessing the uptake of key elements of SRH services and its determinants among adolescents residing in rural districts of Guraghe zone, Southern Ethiopia. A multi-stage method of sampling was employed, and adolescents have been randomly chosen and participated in the study. Pre-tested structured questionnaires were used for data collection. Statistical significance between dependent and independent variables was checked by using bivariate analysis across ANOVA and independent t-tests. To see the weight of each explanatory variable on SRH service utilization, a generalized linear regression model (GLM) with a Poisson link was done. The overall uptake of SRH services was found to be low in the study area. Comprehensive sexuality education (55.1%) and voluntary HIV/AIDS counseling and testing (51.0%) were the commonest service items used by adolescents, while the provision of contraceptives was the lowest service item received (25.9%). Educational level, having a parental discussion, lack of youth clubs, and knowledge of SRH issues were identified as significant predictors of the uptake of key elements of SRH services. Schools should be an excellent means of educating adolescents to increase their knowledge of key elements of SRH services. Furthermore, stakeholders must work together to improve the culture of parental discussion with adolescents and establish and strengthen youth clubs, as measures for encouraging the use of SRH services.